2015
DOI: 10.1016/j.ebiom.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Superinfection and Clinical Progression in Hepatitis B Patients

Abstract: Hepatitis E virus (HEV) infection may cause acute hepatitis and lead to hepatic failure in developing and developed countries. We studied HEV seroprevalences in patients with hepatitis B virus (HBV) infection to understand the consequences of HEV superinfection in a Vietnamese population. This cross-sectional study was conducted from 2012 to 2013 and included 1318 Vietnamese patients with HBV-related liver diseases and 340 healthy controls. The case group included patients with acute (n = 26) and chronic hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 43 publications
3
60
0
1
Order By: Relevance
“…On one hand, the underlying CHB could predispose the co-infected patients to more severe symptoms than HEV mono-infections[10,11]. On the other hand, HEV infection may also aggravate the clinical outcome of HBV infection, especially under conditions of liver cirrhosis[26]. Notably, HEV super-infections were reported as the second most prevalent precipitating factor in triggering ACLF in CHB patients[27,28], revealing a mutual influence among the viral co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the underlying CHB could predispose the co-infected patients to more severe symptoms than HEV mono-infections[10,11]. On the other hand, HEV infection may also aggravate the clinical outcome of HBV infection, especially under conditions of liver cirrhosis[26]. Notably, HEV super-infections were reported as the second most prevalent precipitating factor in triggering ACLF in CHB patients[27,28], revealing a mutual influence among the viral co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…Vietnam is a South-East Asian country with a high prevalence of HBV infection and approximately 10–20% of general populations live with chronic hepatitis B [29, 30]. High prevalence of HDV is reported in HBsAg positive patients in Northern provinces of Vietnam, especially in patients with acute hepatitis B with up to 43% [31].…”
Section: Introductionmentioning
confidence: 99%
“…38% has been reported in previous studies in China (34)(35)(36)(37)(38). In Southeast Asia, the HBV-HEV superinfection rate was reported to be 45%, 14% and 9.5% in Vietnam, India and Bangladesh, respectively (39)(40)(41). A clear territory-wise distribution of HBV-HEV superinfection has been observed in Africa where a higher prevalence of 56.7% was reported in Egypt in the northern part of the continent, while insignificant rates of 1% and 0% were reported in Kenya, the Eastern part of Africa (27,42,43) (Table 1).…”
Section: Epidemiologymentioning
confidence: 66%
“…Other features such as accelerated rates of liver injury, a progression of HBV-related CLD to more severe forms and rapid decompensation to liver failure have also correlated with HEV superinfection in CHB patients. In a recent large Vietnamese survey by Hoan et al (39), HEV seropositivity was found to be associated with the presence of liver cirrhosis and HCC among CHB patients. The poor prognosis of cirrhotic patients based on the Child-Pugh score also correlated with HEV superinfection in this study.…”
Section: Clinical Featuresmentioning
confidence: 93%